Baboon vocal repertoires and the evolution of primate vocal diversity. Issue 126 (January 2019) - Hammerschmidt, Kurt; Fischer, Julia
Abstract: A remarkable and derived trait of humans is the faculty for language, and considerable research effort has been devoted to understanding the evolution of speech. In contrast to spoken language, which constitutes a (learned) symbolic communication system, the acoustic structure of nonhuman primate vocalizations is largely genetically fixed. Yet, appreciable differences between different genera and species may exist. Environmental conditions, sexual selection, and characteristics of the social system have been invoked to explain these differences. Here, we studied the acoustic variation of call types and vocal repertoires in the genus Papio . Because the genus comprises both stable groups as well as multi-level societies, and reveals striking variation in the degree of aggressiveness from south to north, it constitutes a promising model to assess the link between social system characteristics and vocal communication. We found that, the vocal repertoires of the different species were composed of the same general call types. A quantitative analysis of the acoustic features of the grunts and loud calls of chacma ( Papio ursinus ), olive ( P. anubis ), and Guinea ( P. papio ) baboons showed subtle acoustic differences within call types, however. Social system characteristics did not map onto acoustic variation. We found no correlation between the structure of grunts and geographic distance; the same was true for female loud calls. Only for male loud calls from three populations, call structure varied with geographic distance. Our findings corroborate the view that the structure of nonhuman primate vocalizations is highly conserved, despite the differences in social systems. Apparently, variation in rate and intensity of occurrence of signals, probably due to different behavioral dispositions in species, are sufficient to allow for plasticity at the level of the social relationships, mating patterns, and social organization.